Indonesia Economic Quarterly, March 2014 : Investment in Flux - World Bank (Washington, DC, 2014)
Indonesia's economy continues to adjust to weaker terms of trade and tighter external financing conditions, with the composition of growth tilting more towards net exports, and economic growth slowing moderately. While this shift is positive for macroeconomic stability, it has to date been based primarily on tighter monetary policy and the depreciation of the Rupiah in 2013, the effects of which are continuing to play out. To further reduce Indonesia's vulnerability to external shocks, to minimize the risks of a more marked cyclical slowdown in growth, and to convert the near-term macro adjustment into strong, sustained growth over the longer term, further progress on long-standing policy priorities is warranted. Progress in three key areas can support both near-term macro stability and Indonesia's long-term economic prospects. First, there is a need to support domestic and foreign investor confidence. Recent policy and regulatory developments, including the partial ban on mineral exports, have increased uncertainty, may weigh on investment across the economy, and compound the usual difficulty of predicting policy ahead of elections. Given rising fiscal pressures from slower revenue growth and higher fuel subsidy costs, the second priority is to broaden the revenue base and improve the quality of spending, notably by reducing energy subsidy expenditure. These measures would also increase available fiscal space for more equitable, pro-growth spending. Third, credible progress is needed on addressing structural impediments to stronger and more inclusive growth, namely infrastructure and worker skills gaps, and factor and product market constraints. The policy environment is naturally constrained ahead of legislative elections in April and the presidential election in July. However, in light of ongoing economic risks and Indonesia's ambitious development agenda, laying the groundwork for future reforms, minimizing policy uncertainty, and making continued reform progress in some areas, should remain a priority.